2017
DOI: 10.3389/fnins.2017.00455
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Inwardly Rectifying Potassium (GIRK) Channel Activation by the p75 Neurotrophin Receptor Is Required for Amyloid β Toxicity

Abstract: Alzheimer's disease is characterized by cognitive decline, neuronal degeneration, and the accumulation of amyloid-beta (Aβ). Although, the neurotoxic Aβ peptide is widely believed to trigger neuronal dysfunction and degeneration in Alzheimer's disease, the mechanism by which this occurs is poorly defined. Here we describe a novel, Aβ-triggered apoptotic pathway in which Aβ treatment leads to the upregulation of G-protein activated inwardly rectifying potassium (GIRK/Kir3) channels, causing potassium efflux fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Then, Aβ 1–42 modulation of GirK channel might be found analyzing specific regions of the hippocampus (immunohistochemical approach), but it could not be observed in the hippocampus as a whole (western blot analysis). Nevertheless, present data suggest that GirK channels can be taken into account to explain some of the effects of Aβ 1–42 (May et al, ; Nava‐Mesa et al, ; Sanchez‐Rodriguez et al, , ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Then, Aβ 1–42 modulation of GirK channel might be found analyzing specific regions of the hippocampus (immunohistochemical approach), but it could not be observed in the hippocampus as a whole (western blot analysis). Nevertheless, present data suggest that GirK channels can be taken into account to explain some of the effects of Aβ 1–42 (May et al, ; Nava‐Mesa et al, ; Sanchez‐Rodriguez et al, , ).…”
Section: Discussionmentioning
confidence: 91%
“…However, in this study, we found that in hippocampal slices incubated with Aβ 1–42 , protein expression pattern for GIRK1 and 2 subunits did not change. It has been reported that excitotoxic oligomeric Aβ 1–42 may cause a rapid redistribution of existing GirK subunits to the membrane surface (May et al, ), which could explain that protein expression did not seem to change. On the other hand, the immunohistochemical analysis of GIRK1 subunit in the dorsal hippocampus of our different experimental groups showed a significant modulation of GIRK1 protein expression levels, increasing when channel is blocked by TQ, whereas decreasing when opened by ML297, as expected for neuronal drug sensitization and desensitization processes, respectively (Golan, Armstrong, & A.W., A., ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We can speculate that this evidence may be due to two contrasting effects of Aβ on these channels in a more complex neuronal network. Indeed, it has been reported that this peptide led to a GIRK3 channel upregulation, which resulted in K + efflux from neurons triggering, thus, the Aβ-mediated apoptotic pathway [26]. On the contrary, other authors reported an opposite effect of Aβ in which it modulated GIRK3 expression by downregulating these channels [14].…”
Section: Discussionmentioning
confidence: 99%